ANALISIS TERHADAP PELANGGARAN RESOLUSI DEWAN KEAMANAN PBB NOMOR 478 TAHUN 1980 (STUDI KASUS UNILATERAL PROCLAMATION AMERIKA SERIKAT ATAS STATUS KOTA YERUSALEM) - Radid Nugroho Dewantoro (BELLI AC PACIS (Jurnal Hukum Internasional), 2024)
This research aims to analyze the sanctions that can be applied to the United States for violations of international law arising as a result of the unilateral proclamation announced by President Donald Trump on December 6, 2017 as its foreign policy that recognizes Jerusalem as the capital of Israel and moves its embassy from Tel Aviv to Jerusalem. This type of research is prescriptive normative in order to identify sanctions to the United States that has violated international law.The result of this research showed that violations of international law on the United States unilateral proclamation regarding the status of the City of Jerusalem may be subject to various sanctions by the UN Security Council including economic sanctions, diplomatic sanctions, sports sanctions, individual sanctions, and sanctions to suspend privileges as a member of the United Nations. Of the various sanctions that can be applied by the UN Security Council, there are obstacles that can be found, namely the veto rights of permanent members of the Security Council. Therefore it is recommended to countries that have economic stability and geopolitical conditions more or less the same as the United States such as China in order to impose political sanctions in the form of unilateral economic and diplomatic sanctions.